Estabilidade assintótica global para equações diferenciais no plano - Peixoto, Magda da Silva (1999)
Let x! = f(x) be a system of differential equations in the plane where / is C1. This work gives sufficient conditions which guarantee that the basin of attraction of an equilibrium point is the plane. This monograph reports the contribuition given by Gasull, Llibre e Sotomayor to the problem. The above work presents some useful technics to the general problem.